A protocol for assessing the readiness for practicing introspective meditations (manan dhyana) as a tool for reduction of stress among high-stress occupations - Manoj SHARMA (GIornale Italiano di Psicologia e Medicina del Lavoro, 2021)
Stress is inescapable in contemporary times.The workplace offers unique challenges and some spe- cific stressors are unique to working which if not managed can lead to a plethora of negative seque- lae. Some occupations are particularly prone to high stress and burnout. Spirituality at workplace could be used to address poor mental health outcomes. The purpose of this article is to introduce to the researchers a theory-based protocol for assessing the readiness toward practicing intro- spective meditations (manan dhyana), an Eastern approach based on yoga, to combat occupational stress in high-stress professions. The protocol utilizes the multi-theory model (MTM) of health behavior change and presents a questionnaire based on it for administration in a cross-sectional survey design to test the model. If the model is found to be significant then it can be used to design interventions that promote introspective meditations (manan dhyana) for high-stress occupations. Such interventions can first be pilot tested, then tested for efficacy, and finally, if found efficacious, can be replicated in effectiveness studies. This kind of intervention can be used in the framework of workplace health programs to advance worker’s mental well-being.